Oxygen diffusion analysis in a new β Ti–25Ta–40Zr alloy using mechanical spectroscopy technique - Kuroda, Pedro Akira Bazaglia; da Silva, Marcos Ribeiro; Afonso, Conrado Ramos Moreira; Grandini, Carlos Roberto [UNESP] (Elsevier, 2023)
This study primarily focuses on analyzing anelastic processes due to interstitial oxygen in the Ti–25Ta–40Zr alloy. From the structural and microstructural characterization (DRX and optical microscopy), it was detected that the Ti–25Ta–40Zr alloy is a α + β type. Peaks of anelastic relaxation were visualized in the Ti–25Ta–40Zr alloy, where the peaks are thermally activated, with the shift of Qp−1 to higher temperatures in tests performed at high frequencies. The activation energy (E), relaxation time (τ0), and diffusivity (Do) of oxygen in the alloy were obtained E = (0.49 ± 0.02) eV, τ0 = (6.3 ± 0.2) x10−19 s and D0 = (5.0 ± 0.1) x10−3 m2/s.
Keywords: Anelastic relaxation; Dynamic mechanical analysis; Oxygen diffusion; Ti–25Ta–40Zr alloy